EARNINGS MANAGEMENT AND PERFORMANCE: SHARIA VIS-A-VIS NON-SHARIA FIRMS - Hanafi, Rustam; Sutapa, Sutapa (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Earnings management and firm performance are crucial issues in corporate governance, particularly in contexts where ethical considerations intersect with financial practices. This study addresses a research gap by comparing earnings management practices and performance between Sharia and non-Sharia firms in Indonesia, a country with a majority Muslim population. The study analyzes data from firms listed on the Indonesia Stock Exchange during the 2015–2021 period, comprising 2,247 observations. Using independent t-tests, the findings reveal that Sharia firms engage in significantly lower earnings management compared to non-Sharia firms. Furthermore, Sharia firms demonstrate superior performance metrics. These results highlight the potential advantages of adopting Sharia-based governance principles, suggesting that such practices contribute to higher-quality financial reporting and improved firm performance. The study underscores the importance of integrating Sharia values into corporate governance frameworks to enhance ethical and financial outcomes